Community and Tourist Responses to the Innovation of Traditional Goara-Goara Games as Sports Tourism - Muhamad Tsalistudin; aji_putra, ranu baskora; pramono, harry (Journal of Physical Education and Sports, 2025)
The rapid development and advancement of digital technology has made people lazy to move and abandon traditional games. Many efforts have been made in the context of conserving traditional games, one of which is through the goara-goara game. This study aims to determine and analyze the community's response to the goara-goara game as a conservation effort and to develop sport tourism in Magelang Regency. This research method uses a mixed method approach with a sequential explanatory design. The use of this sequential explanatory design is expected that quantitative research data sourced from community questionnaires can be strengthened from qualitative data through interview results, so that the research results can be satisfactory. The findings of the research show that the community's response to the Goara-Goara game is very positive and shows high appeal. This goara-goara game is considered very interesting, fun, competitive, educational and conservative because there are many elements contained in the game such as strength, agility, speed, balance, endurance, accuracy and patience. The conclusion of this study is that the Goara-goara game is very interesting and worthy of being further developed in tourist villages as sport tourism.